Prevalence, clinical course, and predictive factors of immune checkpoint inhibitor monotherapy‐associated hepatitis in Japan. Issue 10 (31st March 2020) - Kitagataya, Takashi; Suda, Goki; Nagashima, Kazunori; Katsurada, Takehiko; Yamamoto, Koji; Kimura, Megumi; Maehara, Osamu; Yamada, Ren; Shigesawa, Taku; Suzuki, Kazuharu; Nakamura, Akihisa; Ohara, Masatsugu; et al.
Abstract: Background and Aim: Immune checkpoint inhibitors (ICI) have revolutionized anti‐malignancy therapy and thus have been increasingly used. Although ICI may cause immune‐related adverse events (irAE) in various organs, including the liver, the prevalence and predictive factors of irAE have not been clarified. Methods: In this retrospective study, consecutive patients who had malignancies and were treated with ICI without other chemotherapeutic agents at Hokkaido University Hospital between 2014 and 2019 were screened. Patients were excluded if they were < 20 years old and had insufficient clinical data. Results: Of the 233 patients screened, 202 patients met the inclusion criteria and were included in the analysis. The patients were aged 25–92 years, and 60.9% were male. The patients received nivolumab ( n = 137), pembrolizumab ( n = 45), ipilimumab ( n = 17), atezolizumab ( n = 2), and avelumab ( n = 1). The prevalence of any grade and grade ≥ 3 irAE hepatitis was 8.4% (17/202) and 4.0% (8/202), respectively. irAE hepatitis occurred at a median duration of 42 days in any grade and 36 days in grade ≥ 3 after ICI initiation. The clinical course of grade ≥ 3 irAE hepatitis was generally favorable; however, 50% required corticosteroid treatment and two patients required additional mycophenolate mofetil. Female sex and history of ICI treatment were significantly associated with the incidence of grade ≥ 3 irAE hepatitis. Conclusions: Grade ≥ 3 irAE hepatitis was observed in 4.0% of the patients who were treated with ICI. Female sex and history of ICI treatment were significantly associated with the incidence of grade ≥ 3 irAE hepatitis.